2014
DOI: 10.3389/fnsyn.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific mechanisms of D-serine uptake and release in the brain

Abstract: Accumulating evidence during the last decade established that D-serine is a key signaling molecule utilized by neurons and astroglia in the mammalian central nervous system. D-serine is increasingly appreciated as the main physiological endogenous coagonist for synaptic NMDA receptors at central excitatory synapses; it is mandatory for long-term changes in synaptic strength, memory, learning, and social interactions. Alterations in the extracellular levels of D-serine leading to disrupted cell-cell signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 102 publications
1
89
1
Order By: Relevance
“…Accumulating evidence suggests both neuronal and glial sources of D-serine synthesis, but recent studies point to different mechanisms of release. In astrocytes, evidence of calcium-dependent vesicular D-serine release has been reported in the hippocampus (Henneberger et al, 2010;Martineau et al, 2014) and calcium-independent D-serine release via pannexin-1 hemichannels has been reported in astrocyte cultures (Pan et al, 2015). In contrast, amino acid transporters have been implicated in neuronal D-serine release .…”
Section: Elevated Levels Of D-serine Results In Enlarged Visual Receptmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests both neuronal and glial sources of D-serine synthesis, but recent studies point to different mechanisms of release. In astrocytes, evidence of calcium-dependent vesicular D-serine release has been reported in the hippocampus (Henneberger et al, 2010;Martineau et al, 2014) and calcium-independent D-serine release via pannexin-1 hemichannels has been reported in astrocyte cultures (Pan et al, 2015). In contrast, amino acid transporters have been implicated in neuronal D-serine release .…”
Section: Elevated Levels Of D-serine Results In Enlarged Visual Receptmentioning
confidence: 99%
“…Determining the functional source of D-serine remains a topic of extensive investigation (Ehmsen et al, 2013;Martineau et al, 2013;Balu et al, 2014;Martineau et al, 2014). Accumulating evidence suggests both neuronal and glial sources of D-serine synthesis, but recent studies point to different mechanisms of release.…”
Section: Elevated Levels Of D-serine Results In Enlarged Visual Receptmentioning
confidence: 99%
“…For instance, the results don’t necessarily mean that gliotransmitters are released directly through Cx43 HCs. Open HCs can facilitate Ca 2+ entry (Schalper et al, 2010) that in turn could trigger Ca 2+ -dependent exocytosis of gliotransmitters indirectly (Martineau et al, 2014). Indeed, the exocytotic secretory machinery (e.g., soluble N-ethyl maleimide-sensitive fusion protein attachment protein receptor (SNARE) complex) is present in astrocytes (Hamilton, 2010) and astrocytic Ca 2+ -dependent exocytosis of glutamate, D-serine and ATP has been described in literature (Harada et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate [and to a lesser degree aspartate (Chen et al, 2005;Patneau and Mayer, 1990)] activates excitatory glutamate receptors, with swelling-induced release of glutamate thought to play a role in pathological conditions such as stroke and spreading depression (Akita and Okada, 2014). D-serine, a co-activator of ionotropic glutamate receptors (Mothet et al, 2000), has also been suggested as potential VRAC substrate (Martineau et al, 2014;Rosenberg et al, 2010), whereas there is no clear evidence for VRAC-dependent transport of the inhibitory neurotransmitter GABA (Franco et al, 2001). Disruption of LRRC8 genes can now be used to stringently assess whether these compounds are transported by VRACs.…”
Section: Introductionmentioning
confidence: 99%